Assessing posttraumatic stress disorder in children with mild to borderline intellectual disabilities - Liesbeth Mevissen; Robert Didden; Hubert Korzilius; Ad de Jongh (European Journal of Psychotraumatology, 2016)
Background: Evidence suggests that children with mild to borderline intellectual disabilities (MBID; IQ 50–85) have an elevated risk for both being exposed to potentially traumatic events and developing a posttraumatic stress disorder (PTSD). In this target group, PTSD often remains undiscovered due to a lack of diagnostic instruments. Valid instruments for the assessment of PTSD in children with MBID are therefore needed. Objective: The aim of the current study was to validate the adapted PTSD section of the Anxiety Disorders Interview Schedule for Children (ADIS-C) for the assessment of PTSD in children with MBID according to DSM-IV-TR and DSM-5 criteria. Method: Eighty children (aged 6–18 years) with MBID who were referred to an outpatient psychiatric service and their primary caregivers were interviewed using the adapted ADIS-C. Results: The adapted ADIS-C PTSD section has excellent interrater reliability and good convergent validity. PTSD symptoms described spontaneously by children with MBID and their caregivers closely matched those included in the DSM-IV-TR and DSM-5. Many of the children who met Criterion A did not meet PTSD symptom criteria. Conversely, children meeting the full PTSD criteria were more likely than other children with MBID to have been exposed to at least one traumatic event meeting Criterion A and to a higher total number of potentially traumatic events. Conclusions: The results support the reliability and validity of the adapted ADIS-C PTSD section for assessing PTSD in children with MBID. The use of this clinical interview helps to improve detection of PTSD and subsequent access to trauma-focused interventions for this at risk target group.